Pemikiran Politik Islam Klasik dan Relevansinya Bagi Demokrasi Modern: Penelitian - Imam Solehudin; Rina Setyaningsih; Lestari; Pandu Winata, Bayu; Hilmi, Masdar; Ismail; Supadi, Ari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Classical Islamic political thought represents an intellectual legacy that emerged from the Muslim community’s struggle to manage power, law, and society from the era of the Khulafāʾ al-Rāsyidīn to the dynastic periods. Concepts such as shūrā (consultation), justice, and imāmah (leadership) serve as normative foundations for governance from an Islamic perspective. This article aims to examine the key ideas of classical Islamic political thought and analyze their relevance to the modern democratic system. The research employs a library study method with a historical-philosophical analytical approach. The findings indicate that the principle of shūrā aligns closely with participatory democracy, although it differs in theological foundations. Moreover, the classical scholars’ notions of social justice and leadership accountability remain highly relevant to contemporary governance. Thus, classical Islamic political thought should not be viewed merely as a historical doctrine but as an ongoing source of inspiration for developing a more ethical and just form of democracy.